Immunomodulatory effects of probiotic Lactobacillus brevis ZG2488 on SARS-CoV-2 vaccine responses in mice - Chen, Mengshan; Cao, Zhijie; Chen, Yulu; Ren, Zhihong; Lu, Simin; Pu, Danna; Zhang, Sihui; Zhang, Gui; Yang, Jing; Pu, Ji; Xu, Jianguo (Frontiers in Microbiology, 2025)
IntroductionThis study investigates the immunoenhancing effects of the probiotic Lactobacillus brevis ZG2488 on an adenovirus-vectored SARS-CoV-2 vaccine (AdC68-Delta-S) in mice.MethodsMice were administered ZG2488 in combination with AdC68-Delta-S. Immune responses were evaluated by measuring SARS-CoV-2-specific IgG in bronchoalveolar lavage fluid (BALF), IFN-γ secretion by splenocytes, and transcriptomic and CIBERSORT analyses of splenic immune cells.ResultsZG2488 intervention significantly enhanced local mucosal humoral immunity in the respiratory tract (increased SARS-CoV-2-specific IgG in BALF) and systemic Th1 cellular immunity (increased IFN-γ secretion by splenocytes). Transcriptomic analysis revealed upregulation of the JAK-STAT signaling pathway, antigen processing and presentation pathways, and pro-inflammatory pathways (IL-17/TNF/NLR/PI3K-Akt), alongside downregulation of hyperinflammation-associated pathways. CIBERSORT analysis showed that ZG2488 reshaped splenic immune cell composition, increasing memory CD4+ T cells, Th1 cells, and dendritic cells (DCs), while decreasing macrophages, follicular helper T (Tfh) cells, monocytes, and γδ T cells.DiscussionThese findings demonstrate that L. brevis ZG2488 enhances the immune response to the SARS-CoV-2 vaccine through synergistic and multi-mechanistic actions, supporting its potential as a probiotic adjuvant strategy.